Dysbiotic tumor microbiota associates with head and neck squamous cell carcinoma outcomes. (January 2022) - Dou, Yu; Ma, Chao; Wang, Ketao; Liu, Shaohua; Sun, Jintang; Tan, Wanye; Neckenig, Markus; Wang, Qingjie; Dong, Zuoqing; Gao, Wenjuan; Chen, Anwei; Zhang, Dong; et al.
Highlights: Tumor microbiota differs between HNSCC patients with distinct survivals. Microbial dysbiosis index associates with outcomes of HNSCC patients. Tumor microbiota might correlate with peritumoral inflammatory infiltration. Abstract: Background: The need for an effective tool to predict prognosis of head and neck squamous cell carcinoma (HNSCC) patients is critical and unmet. Microbiota has recently been found involved in tumor progression and response to immunotherapy. However, the association of microbiota with the prognosis of HNSCC patients remains obscure. This study aims to investigate the association between tumor microbiota and outcomes of HNSCC patients. Methods: A retrospective study including 129 primary tumors of HNSCC was conducted. Using 16S rRNA sequencing, the profile and the composition of tumor microbiota were measured and their associations with overall survival (OS) and disease free survival (DFS) were examined. Results: We observed a reduced richness and enriched abundances of genera Schlegelella and Methyloversatilis in tumor microbiota of HNSCC patients with poor prognosis. However, a richer tumor microbiota with greater abundances of genera Bacillus, and  Lactobacillus  and  Sphingomonas was characterized in the patients with favorable prognosis.The ratio of these differentially abundant taxa, microbial dysbiosis index (MDI), was significantly associated with OS (hazard ratio [HR], 4.67, 95% confidence interval [CI], 2.51 to 8.69, P  < 0.001) and DFS (HR, 2.89; 95% CI, 1.74 to 4.80,   P  < 0.001) independently of age, tumor size, lymph node metastasis, differentiation and p16 status. The risk score of multivariate Cox regression exhibited an excellent performance for estimating three-year OS (AUC of 0.826). We also found a richer tumor microbiota was correlated with moderate peritumoral inflammatory infiltration. Conclusion: These results indicate that tumor microbiota associates with outcomes of HNSCC patients.